2013
DOI: 10.1210/jc.2012-2555
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ and Tumor Necrosis Factor-α Sustain Secretion of Specific CXC Chemokines in Human Thyrocytes: A First Step Toward a Differentiation between Autoimmune and Tumor-Related Inflammation?

Abstract: These results confirm that human thyrocytes secrete CXC chemokines and demonstrate that the secretion of CXCL8 and CXCL10 is sustained by specific proinflammatory cytokines or their combination, which ultimately determines the nature of the infiltrating lymphocytes in human thyroid diseases. These results indirectly support a major role for CXCL10 in thyroid autoimmunity whereas CXCL8 might be involved in tumor-related inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 32 publications
5
35
0
Order By: Relevance
“…In the present study, positivity of anti-TPO antibodies in the serum of patients was Although Qing et al [1] reported no relationship between the density of CD68 expressing TAMs and LT, which is one aspect of the immune response, our results revealed that the percentage of TAMs was higher in the tumors without surrounding LT. Additionally, the presence of concomitant LT was inversely correlated with the significance of LTR, LVI, LNM, and larger tumor size. These data may support the results of Rotondi et al [32], which indicated different chemokine expression of the tumor-associated lymphocytic response and the autoimmune lymphocytic response. However, the immunophenotype of these lymphoid cells was not evaluated in this study, so these results may be possible signs of the interactions between TAMs and lymphoid cells associated with the immunosuppressive effects of these polarized macrophages.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, positivity of anti-TPO antibodies in the serum of patients was Although Qing et al [1] reported no relationship between the density of CD68 expressing TAMs and LT, which is one aspect of the immune response, our results revealed that the percentage of TAMs was higher in the tumors without surrounding LT. Additionally, the presence of concomitant LT was inversely correlated with the significance of LTR, LVI, LNM, and larger tumor size. These data may support the results of Rotondi et al [32], which indicated different chemokine expression of the tumor-associated lymphocytic response and the autoimmune lymphocytic response. However, the immunophenotype of these lymphoid cells was not evaluated in this study, so these results may be possible signs of the interactions between TAMs and lymphoid cells associated with the immunosuppressive effects of these polarized macrophages.…”
Section: Discussionsupporting
confidence: 92%
“…One of the most recent reports states that IL-10 overexpressing B cells may act as regulatory T cells and may inhibit antigen-specific T cell responses [31]. Rotondi et al [32] reported that TNF-α-induced chemokine (C-X-C motif) ligand 8 (CXCL8) secretion might play a role in tumor-related inflammation rather than autoimmunity-related inflammation in the thyroid gland. We have also previously reported that lymphocytic tumor response is a predictive factor for lymph node metastasis in papillary thyroid carcinoma, whereas LT is a protective factor [2].…”
Section: Discussionmentioning
confidence: 99%
“…While other studies reported an increased rate of benign nodules associated with FNMTC (22), the higher prevalence of thyroiditis in the present cohort may be partially explained by the higher frequency of familial tumors in females (Table II). However, it is intriguing to speculate that chronic autoimmune thyroiditis, associated with lymphocyte infiltration and cytokine production (23,24), may represent a favorable milieu for the development of thyroid malignancies, as suggested for sporadic carcinomas (25). Since specific genetic loci have been associated with the risk of developing chronic autoimmune thyroiditis (26), the present data suggest that common genetic predisposing factors may be involved in either autoimmune thyroiditis or thyroid carcinomas.…”
Section: Discussionmentioning
confidence: 63%
“…Recombinant IFNg treatment was subsequently tested to treat a variety of tumors: chronic myelogenous leukemia, bladder carcinoma, colorectal cancer, melanoma, ovarian cancer, and adult T-cell leukemia, but the results were considerably heterogeneous (Kurzrock et al 1987, Kloke et al 1992, Miller et al 2009, suggesting that IFNg has, in fact, two faces: it can have cytostatic/cytotoxic and cytoproliferative effects, depending on the context, similar to transforming growth factor b (TGFb (TGFB1)) and TNF, which also display this kind of dual contrasting behaviors (Roberts & Wakefield 2003, Wajant 2009 Kimura et al 2005Kimura et al , 2009). In a recent study, Rotondi et al (2013) have shown that IFNg stimulates the secretion of CXCL10, a situation associated with Th1 T-cell infiltration typical of autoimmune thyroid disease (AITD), which is closely related to thyroid tumors, leading, in most cases, to a better prognosis of patients , 2012. Conversely, the administration of TNFa has been shown to lead to high levels of CXCL8 (IL8), a chemokine that is not primarily involved in thyroid autoimmunity, but that might induce tumor-related inflammatory infiltrating lymphocytes in thyroid diseases.…”
Section: Interferon Gmentioning
confidence: 91%
“…These studies provide evidences that the production of TNFa in the tumor microenvironment can lead to direct DNA damage; has an apoptotic or antiapoptotic role and, depending on downstream signaling, mitogenic activity; can mediate tumor cell/stroma relationships; and can induce other cytokines and chemokines that promote tumor development (Vendramini-Costa & Carvalho 2012). Zhang et al (2013) have recently demonstrated that the administration of thyroid-stimulating hormone (TSH) can increase TNFa expression, which has already been reported to be related to the chemokine profile of tumor inflammation, possibly indicating that TNFa might play an indirect role in thyroid tumors by the inflammation that it stimulates (Rotondi et al 2013). In Graves' disease, inflammatory mediators, such as ILs and TNFa, stimulate the production of external thyroid-stimulating antibodies that bind to the TSH receptor (Baur et al 2000, Davis 2008).…”
Section: Tumor Necrosis Factormentioning
confidence: 99%